Does a Wii-based exercise program enhance balance control of independently functioning older adults? A systematic review - Laufer Y (Dove Medical Press, 2014)
Yocheved Laufer, Gali Dar, Einat Kodesh Physical Therapy Department, Faculty of Social Welfare and Health Sciences, University of Haifa, Haifa, Israel Background: Exercise programs that challenge an individual’s balance have been shown to reduce the risk of falls among older adults. Virtual reality computer-based technology that provides the user with opportunities to interact with virtual objects is used extensively for entertainment. There is a growing interest in the potential of virtual reality-based interventions for balance training in older adults. This work comprises a systematic review of the literature to determine the effects of intervention programs utilizing the Nintendo Wii console on balance control and functional performance in independently functioning older adults.Methods: Studies were obtained by searching the following databases: PubMed, CINAHL, PEDro, EMBASE, SPORTdiscus, and Google Scholar, followed by a hand search of bibliographic references of the included studies. Included were randomized controlled trials written in English in which Nintendo Wii Fit was used to enhance standing balance performance in older adults and compared with an alternative exercise treatment, placebo, or no treatment.Results: Seven relevant studies were retrieved. The four studies examining the effect of Wii-based exercise compared with no exercise reported positive effects on at least one outcome measure related to balance performance in older adults. Studies comparing Wii-based training with alternative exercise programs generally indicated that the balance improvements achieved by Wii-based training are comparable with those achieved by other exercise programs.Conclusion: The review indicates that Wii-based exercise programs may serve as an alternative to more conventional forms of exercise aimed at improving balance control. However, due to the great variability between studies in terms of the intervention protocols and outcome measures, as well as methodological limitations, definitive recommendations as to optimal treatment protocols and the potential of such an intervention as a safe and effective home-based treatment cannot be made at this point. Keywords: virtual reality, exergame, balance, exercise, falls